Estrogenic Plants: to Prevent Neurodegeneration and Memory Loss and Other Symptoms in Women After Menopause - Moran, Valentina E.; Echeverria, Florencia; Barreto, George E.; Echeverria, Javier; Mendoza, Cristhian (Frontiers in Pharmacology, 2021)
In mammals, sexual hormones such as estrogens play an essential role in maintaining brain homeostasis and function. Estrogen deficit in the brain induces many undesirable symptoms such as learning and memory impairment, sleep and mood disorders, hot flushes, and fatigue. These symptoms are frequent in women who reached menopausal age or have had ovariectomy and in men and women subjected to anti-estrogen therapy. Hormone replacement therapy (HRT) alleviates menopause symptoms; however, it can increase cardiovascular and cancer diseases. In the search for therapeutic alternatives, medicinal plants and specific synthetic and natural molecules with estrogenic effects have attracted widespread attention between the public and the scientific community. Various plants have been used for centuries to alleviate menstrual and menopause symptoms, such as Cranberry, Ginger, Hops, Milk Thistle, Red clover, Salvia officinalis, Soy, Black cohosh, Turnera diffusa, Ushuva, and Vitex. This review aims to highlight current evidence about estrogenic medicinal plants and their pharmacological effects on cognitive deficits induced by estrogen deficiency during menopause and aging.